PERBANDINGAN MINAT BELAJAR PENDIDIKAN JASMANI ANTARA SISWA SMAN, SMKN, DAN MAN (STUDI PADA SISWA SMAN, SMKN, DAN MAN SE KEC SAMPANG KAB SAMPANG) - FUAD, AHMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical education becomes an important part in education. Thus, the physical educational should be held in order to achieve that goal. The goal of physical education is not only to develop the physical aspect but also to develop the aspects of health, physical fitness, critical thinking skill, emotional stabilization, social competent, logical thinking and moral through the various activities of physicsand exercise. As one of the lessons in school which has its own aims not only to develop the physical skill but also to monitor the development of the students’ character. The aim of this observation are to know the different interest in joining the lesson of physical education among the students of all the SMAN, SMKN and MAN in Sampang sub district and to know which one is better among them. The object of this observation is the students of all SMAN, SMKN and MAN in Sampang sub district. The method which is used in this observation is descriptive quantitative (non-experimental). The instrument of this observation is using inquiry. The data analysis that is used is Anova. According to the data accounting usingAnova, it can be found that the alpha score is 0,130 so if it is compared with alpha 0,05 (0,130 > 0,05) the result is Ho accepted and Ha refused. It shows that there is no significant difference of the motivation in joining the lesson of physical education among the students of SMAN, SMKN and MAN. The more analysis also shows that the best average score is those who are the students of SMAN 105,13 , the second one is SMKN 103,7 and the last one is MAN 100,29. Keywords: Interest , Physical Education, SMAN, SMKN, MAN